Executive function moderates the effect of reappraisal on life satisfaction: A latent variable analysis - TOH, Wei Xing (Institutional Knowledge at Singapore Management University, 2022)
Emotion regulation strategies, such as reappraisal and suppression, have been shown to dissimilarly affect life satisfaction. Specifically, reappraisal is linked to higher life satisfaction, while suppression is associated with lower life satisfaction. Less is known, however, about the potential moderators of these established relations. Given that reappraisal and suppression are contingent, in part, on executive function (EF), which comprises a group of adaptive, goal-orientated control processes (i.e., inhibitory control, working memory, and shifting), we explored whether different components of EF could moderate the impact of reappraisal and suppression on life satisfaction. Using latent moderated structural equation analyses, we found that the positive contribution of reappraisal to life satisfaction was more pronounced at higher than lower levels of inhibitory control and working memory. Shifting did not moderate the associations of reappraisal and suppression with life satisfaction. Further analyses, however, indicated that the interactive effects of reappraisal with inhibitory control and working memory on life satisfaction were driven primarily by the shared variance among EF constructs (i.e., common EF). Our findings underscore the pivotal role of common EF in moderating the relation of reappraisal with life satisfaction.